P015 The effects of cathodal transcranial direct current stimulation in patienst with focal epilepsy (a pilot study)'. Issue 3 (March 2017) - Zoghi, M.; Cook, M.; O'Brien, T.; Kwan, P.; Jaberzadeh, S.; Galea, M.
Abstract : Introduction: Over 65 million people live with epilepsy worldwide. Unfortunately, seizures can not be adequately controlled in a third of the affected individuals. Therefore, there is a definite need for adjunctive or alternative therapeutic approaches in this group of patients to control the recurrence of seizure attacks. Modulation of dysfunctional electrical brain activity by transcranial direct current stimulation (tDCS) seems to be a potentially valuable non-invasive alternative for epilepsy treatment in this population. Objectives: This pilot study aimed to assess the effects of a novel protocol called within-session repeated c-tDCS (9 min treatment - 20 min rest - 9 min treatment) on patients with focal epilepsy. Method: We conducted a small pilot study in patients admitted to the Video-EEG Monitoring Unit at the Royal Melbourne Hospital and as out patients at this hospital or St Vincent Hospital. Thirty patients have participated in this study to date. Twenty patients with focal epilepsy received one session of c-tDCS (9–20-9 protocol) over the temporal lobe in the affected hemisphere. One participant received c-tDCS on two consecutive days. The other nine patients received one session of sham tDCS with the same electrode montage and protocol. Short interval intracortical inhibition or SICI was measured with paired-pulse transcranial magnetic stimulation (TMS) before and after the tDCS intervention in 18 participants. Motor evoked potentials were recorded from first dorsal interosseous muscle in these participants. Participants were asked to record the time and the number of their seizures post tDCS treatment for 4 weeks in a seizure diary. Twenty-four participants returned their diaries. Results: All patients tolerated the c-tDCS protocol very well. One-way ANOVA showed that SICI was increased significantly in the experimental group compared to the sham group ( F = 10.3, p = 0.005) (Fig. 1). The mean response ratio was −48.4 (SD = 54) for the experimental group vs. −8.3 (SD = 16.7) for sham group . Conclusion: This pilot study is still in progress. Based on the achieved results so far, it can be concluded that c-tDCS can be a promising non-invasive technique that can be used to control seizure attacks.